Hyaluronic acid microneedles‐laden collagen cryogel plugs for ocular drug delivery. Issue 42 (7th April 2020) - Saraswathy, Krishnapriya; Agarwal, Gopal; Srivastava, Akshay
Abstract: Particle loaded hydrogels have shown to provide prolonged delivery of drug in a controlled manner. We propose that embedding drug‐loaded hyaluronic acid (HA) microneedles in supermacroporous collagen type‐I (Col‐I) cryogel plugs may enhance the hydration and provide prolonged release of drug for ocular diseases. In this study, we have fabricated Col‐I cryogel and HA‐microneedles embedded Col‐I cryogel at sub‐zero temperature using 4S‐arm Star‐PEG as a crosslinker. The fabricated novel Col‐I cryogels have shown supermacroporous morphology with solvent uptake capacity of nearly 90% due to large pore volume and high interconnectivity. These features of the cryogel enable the release the drug in a controlled and sustained manner. The fabricated cryogels have demonstrated nearly 50% degradation in simulated tear fluid within 15 days of duration. Moreover, the microneedles incorporated cryogels have shown prolonged release of required therapeutic concentration of drug that may satisfy the present dire need for antibacterial drug delivery in eyes. The variation in the drug release kinetics from Col‐I cryogel and HA‐microneedles‐laden‐Col‐I cryogels have been studied in different release media (PBS and Simulated tear fluid). Abstract :